Combustion of Biogas Released from Palm Oil Mill Effluent and the Effects of Hydrogen Enrichment on the Characteristics of the Biogas Flame - Seyed Ehsan Hosseini; Ghobad Bagheri; Mostafa Khaleghi; Mazlan Abdul Wahid (Journal of Combustion)
Biogas released from palm oil mill effluent (POME) could be a source of air pollution, which has illustrated negative effects on the global warming. To protect the environment from toxic emissions and use the energy of POME biogas, POME is conducted to the closed digestion systems and released biogas is captured. Since POME biogas upgrading is a complicated process, it is not economical and thus new combustion techniques should be examined. In this paper, POME biogas (40% CO2 and 60% CH4) has been utilized as a fuel in a lab-scale furnace. A computational approach by standard k-ε combustion and turbulence model is applied. Hydrogen is added to the biogas components and the impacts of hydrogen enrichment on the temperature distribution, flame stability, and pollutant formation are studied. The results confirm that adding hydrogen to the POME biogas content could improve low calorific value (LCV) of biogas and increases the stability of the POME biogas flame. Indeed, the biogas flame length rises and distribution of the temperature within the chamber is uniform when hydrogen is added to the POME biogas composition. Compared to the pure biogas combustion, thermal NOx formation increases in hydrogen-enriched POME biogas combustion due to the enhancement of the furnace temperature.